Designing Information Systems for Transportation Permit of the Coal Mining Industry Based on Rational Unified Process - Saputra, Hendy Maulana Jaya; Harjanto, Brianto Rovi; Yulizar, Reynaldi; Nur, Rizky Febrian (Universitas Serambi Mekkah, 2020)
Indominco Mandiri Ltd. is a private company engaged in coal mining and general trading. The permit process for the transportation of goods is a vital sub-process in supporting the organization's business activities. The transportation permit process employed by the Indominco Mandiri Ltd. is still the manual one. The present study aimed to develop a Transportation Permit Information System for the company. The rational unified process methodology was employed in the designing process, the system and user requirements, and the system design. The results obtained from working on specific practical work tasks are the business process model, software requirements specifications, and software design documents. The resulting software requirements documents and software design documents were produced based on IEEE Std 830 â„¢ -1998 (R2009) and IEEE Std 1016 â„¢ -2009. The business process modeling was used in the business process notation model. The system requirements were documentedin the software requirements specification based on the use case. The point of view used to design the software was the points of view of composition, logic, dependency, information, and interaction. The diagrammatic models to describe the points of view were a unified modeling language, relationalmodels, data dictionaries, and entity-relationship diagrams. Several processes needed in the transportation permit information system, namely managing form, managing account, validating the form, verifying the form, and managing the register. This research aids developers to develop information systems to suit the needs of the customers. Keywords: rational unified process, business process, software requirement specification, software design description, transportation permit